A comparative study of oribatid mite communities in red wood ant Formica polyctena nests and surrounding soil in a Finnish oak forest. Issue 3 (21st February 2016) - Elo, Riikka Aleksandra; Penttinen, Ritva; Sorvari, Jouni
Abstract: Ant nests are also inhabited by other invertebrates, ant associates. The oribatid mite (Acari: Oribatida) fauna of nests is poorly known, both in terms of abundance and diversity. We compared the oribatid assemblages within and outside red wood ant Formica polyctena nests in a Finnish oak forest. Altogether ten mounds were investigated and comparable samples were collected from adjacent soil 4 m from each mound. A total of 10 529 specimens were recovered, 4959 of them in mounds and 5633 in soil. The specimens represented 74 species (and two higher taxa) belonging to 60 genera and 39 families. Significant differences in abundance or diversity were not observed between nests and soil habitats. For nest samples the abundance of specimens significantly correlated with diversity indicating that mounds form rich habitat patches with a diverse set of niches. Mound size had no effect on community composition. The nest and soil habitats were predominantly occupied by different species resulting in dissimilarities in community composition; 34% of the species showed a preference for nest habitat and 50% for soil habitats, whereas16% were indifferent with equal abundances in both habitats. Nonetheless, most of the species with a preference for nests are frequently found in various habitats in nature, and may be classified as facultative myrmecophiles that maintain populations also in ant nests. Ant nests host abundant and diverse oribatid assemblages, which differ from the fauna in adjacent soil, and wood ants are therefore important factors in maintaining biodiversity.